Inequidad y cáncer : una revisión conceptual (2009)
ABSTRACT: Inequality in health is the generic term used to designate differences, variations and disparities in health status of individuals and groups. The definition issued by the World Health Organization says that inequity in health implies that inequalities are unnecessary, avoidable and unfair. In this sense, it is not enough to describe the inequalities in health outcomes, it is necessary to revise its determinants since their uneven distribution, contributing to inequities. In general, the majority of health inequalities between social groups are unfair because they reflect a distribution, also of unjust social determinants such as access to employment, education, health services, discrimination on ethnic, gender, socioeconomic or immigrant status, etc. Social inequalities in cancer imply disparities in prevention, incidence, prevalence, detection and treatment of cancer burden and its determinants. They are mainly related to differences in living and working conditions, inadequate medical care and social policies that affect social determinants such as occupation, income and educational level, for example. The review suggests that most socially vulnerable populations are more likely to develop cancer, to die from the disease and to suffer without the opportunity of palliative care. This confirms the need to generate knowledge that enables a better understanding of social disparities in the cancer-related context.